The implication of feed-in tariff funding structure and the sustainability of renewable energy in Malaysia - Yusoff, S.; Syafiq Rosli, A. (2015)
With the anticipated increase in energy use and its implication toward sustainable development, Malaysia has put renewable energy at the forefront of Malaysia's energy policy to address environmental issues such as climate change and fossil fuel depletion. Drawing from successful case-studies from around the globe, Malaysia implemented its own version of the Feed-in Tariff (FIT) mechanism in a bid to achieve energy security and environmental prosperity. After three years of success, the growth of the renewable energy market under FIT is under threat due to the small size of the Renewable Energy Fund. Since FIT is funded by electricity consumers, they would need to make a larger contribution to address the issue. The question remains on whether the Malaysian public is willing to pay more. Previous literatures from Europe suggested that large segments of the general population are willing to pay for green electricity. More importantly, existing literatures have mixed reviews on whether attitude towards environment affects WTP. Using theory of planned behavior (TPC), the NIMBY (not-in-mybackyard) attitude towards environment was highlighted in several studies, especially in Malaysian literatures. The application of contingent valuation method (CVM) was demonstrated in literatures from Europe and the United States. However, Malaysian literatures lacks the use ofCVM in their WTP investigations. Finally, recommendation for future studies on WTP for green electricity in Malaysia was put forth with an emphasis on the use of TPC and CVM approach. The outcome of such study would give policy-makers the quantitative evidence to justify any changes to the FIT funding structure